Influence of pyridoxine and spermine on lemon grass (Cymbopogon citratus) plants - SALWA A. ORABI; IMAN M. TALAAT; LAILA K. BALBAA; ABDALLA EL-MOURSI ABDALLA (Smujo International, 2015)
Abstract. Orabi SA, Talaat IM, Balbaa LK, Abdalla AE. 2015. Influence of pyridoxine and spermine on lemongrass (Cymbopogon citratus) plants. Nusantara Bioscience 7: 139-143. Two pot experiments were conducted to investigate the effect of pyridoxine and spermine (each at 50, 100 and 200 mg/L) on plant growth, essential oil yield, and its main constituents. All treatments significantly promoted plant height, fresh and dry mass (g/plant) of Cymbopogon citratus L., especially 100 mg/L spermine which mostly recorded the highest increments in total nitrogen, total phosphorous and total potassium mainly in the second cut, followed by 200 mg/L pyridoxine. Total phenols, essential oil % and oil yield recorded the maximum increments with spermine treatments followed by pyridoxine. Treatment of lemongrass plants with 100 mg/L spermine gave the highest relative percentage of citronellol (51.20%). Oxygenated compounds recorded the highest value (89.70%) with 200 mg/L spermine treatment, while the maximum non-oxygenated ones resulted from the untreated plants (13.65%). All treatments under study significantly affected the scavenging ability of the natural antioxidants of the plant extract towards the stable free radical DPPH (2, 2-diphenyl-1-picrylhydrazyl-hydrate). Application of spermine at the concentration of 100 mg/L recorded the highest increment in phenylalanine ammonia lyase (PAL) enzyme activity (µg/g F.wt.).